"Talking Across Worlds": Classist Microaggressions and Higher Education. Issue 2 (2nd April 2016) - Smith, Laura; Mao, Susan; Deshpande, Anita
ABSTRACT: What can we learn about the existence of classist microaggressions from the experiences of graduate students? What messages do poor and working-class students receive from peers, faculty, and administrators about their inclusion in campus culture? In this qualitative study, narrative data was gathered from 15 graduate students who identified as coming from poor or working-class backgrounds and was analyzed via consensual qualitative research methodology. In addition to describing financial obstacles, participants reported feelings of stigmatization and alienation as challenges to their academic adjustment. The findings affirm the extension of the microaggressions framework to the study of classism and also have implications for the development of enhanced support structures for students from poor and working class backgrounds.